Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History - Kubala, Agata (2021)
The gathering of archival materials always precedes the work on the items in every collection. Unfortunately, many documents have been lost, collections have been scattered, but their impact on culture and science has remained, as a deep interest in the ancient world, including its material products. Perhaps this appeal of the ancient world comes from Italy, thanks to its history, monuments and culture. Among the greatest contributors to spreading knowledge of and fascination with antiquity were painters, especially those who wanted to surround themselves with period objects when creating scenes set in ancient times. There are also collections devoted to classical art and literature. The book I have in front of me is an excellent mirror of antiquity collecting. It presents its history, the reasons for the rise of the fascination with antiquity, the history of individual collections, as well as methods of searching for them. Moreover, almost every article outlines the political circumstances of the time that affected collectors and their actions. This book will most probably find its way to the bookshelves of archaeologists, art historians, historians, museologists, as well as numerous gatherers and collectors.From the review by dr hab. Tomasz Scholl